Membangun Kembali Kepercayaan Masyarakat Pasca Pelanggaran dalam Business to Consumer (B2C) E-Commerce: Studi Empiris di Yogyakarta - Kusuma, Hadri; Sari, Marina Silvia (Jurnal Manajemen Teknologi, 2012)
This paper focuses on the process of rebuilding reputation and the intention level of the community to continue trust after trustees fix their e-commerce systems. This research integrates two previous research models to assess rebuilding post trust violation through system improvement that may influence the intention to continue trust. The objectives of the research are to examine the efforts of rebuilding post trust violation on the Business to Consumer (B2C) E-commerce and test the effect scale of the system improvement on the intention of the customers to continue trust.Ã‚Â Using the data of 267 respondents that experienced trust violations, the result shows that the intention to continue trust was significantly related to the communication improvement, rebuilding trust through system improvement and confirmation by trust restoration. Meanwhile, the variables of the commitment to guarantee, product varieties and third party support were not significantly related to the rebuilding of post-violation trust in B2C electronic commerce. The paper also discusses the implications of the findings both theoretically and practicall in detail. Key Words: Trust, System, Communication, Confirmation. E-commerce